2022
DOI: 10.1080/19490976.2022.2120744
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid induces gastric intestinal metaplasia by activating STAT3 signaling and disturbing gastric bile acids metabolism and microbiota

Abstract: Intestinal metaplasia (IM) is the inevitable precancerous stage to develop intestinal-type gastric cancer (GC). Deoxycholic acid (DCA) is the main bile acid (BA) component of duodenogastric reflux and has shown an increased concentration during the transition from chronic gastritis to IM associated with continued STAT3 activation. However, the mechanisms underlying how DCA facilitates IM in the gastric epithelium need exploration. We evaluated IM and bile reflux in corpus tissues from 161 subjects undergoing G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Several studies have shown that lactobacillus is widely colonized in human gastric mucosa ( Hakalehto et al, 2011 ; Delgado et al, 2013 ). It metabolizes lactose into lactic acid, which acidifies the mucous layer of the stomach and then inhibits the secretion of gastrin and gastric acid by the G cells of the antrum ( Myllyluoma et al, 2007 ; Jin et al, 2022 ). Therefore, a higher relative abundance of Lactobacillus in the gastric microbiome may accelerate gastric mucosal atrophy, IM, and tumorigenesis ( Jin et al, 2022 ).…”
Section: Microbial Communities Associated With the Occurrence Of Immentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that lactobacillus is widely colonized in human gastric mucosa ( Hakalehto et al, 2011 ; Delgado et al, 2013 ). It metabolizes lactose into lactic acid, which acidifies the mucous layer of the stomach and then inhibits the secretion of gastrin and gastric acid by the G cells of the antrum ( Myllyluoma et al, 2007 ; Jin et al, 2022 ). Therefore, a higher relative abundance of Lactobacillus in the gastric microbiome may accelerate gastric mucosal atrophy, IM, and tumorigenesis ( Jin et al, 2022 ).…”
Section: Microbial Communities Associated With the Occurrence Of Immentioning
confidence: 99%
“…It metabolizes lactose into lactic acid, which acidifies the mucous layer of the stomach and then inhibits the secretion of gastrin and gastric acid by the G cells of the antrum ( Myllyluoma et al, 2007 ; Jin et al, 2022 ). Therefore, a higher relative abundance of Lactobacillus in the gastric microbiome may accelerate gastric mucosal atrophy, IM, and tumorigenesis ( Jin et al, 2022 ). In addition, a high abundance of Thermus and Anoxybacillus was also detected in gastric juices of IM patients ( Liu et al, 2022 ).…”
Section: Microbial Communities Associated With the Occurrence Of Immentioning
confidence: 99%
“…In the case of bowel cancer, how FXR regulates tumor growth by affecting energy is worthy of further investigation. DCA activates the STAT3 signaling pathway, interferes with the gastric microbiome and BA metabolism, and induces gastrointestinal metaplasia 105 . DCA reduces the expression of FXR, activates the Wnt signaling pathway, increases the levels of β-catenin and c-Myc, and promotes the proliferation and migration of colon cancer cells.…”
Section: Intestinal Epithelial Cellsmentioning
confidence: 99%
“…In addition, SBAs also promote colorectal tumorigenesis by activating oncogenic pathways including TGR5/STAT3, WNT/β-catenin, and NF-kB signaling. 71–74 A recent study in 2022 reported that SBAs could enhance stemness of CRC stem cells, of which SBAs involving tauro-β-muricholic acid and DCA induce proliferation of Lgr5-expressing cancer stem cells, further driving malignant transformation and promoting the adenoma-carcinoma progression. 75 Consistently, oral administration of DCA to mice led to increased colonic expression of R-spondin 3, an important protein regulating stem cell fate, whereas depletion of R-spondin 3 prevented such DCA-induced stem cell proliferation.…”
Section: Microbial Metabolites In Tumorigenesismentioning
confidence: 99%